GENE-18. PAN-OMIC ANALYSIS OF DIFFUSE INTRINSIC PONTINE GLIOMA FROM CHILDREN ENROLLED IN THE PNOC003 PRECISION MEDICINE TRIAL IDENTIFIES OPPORTUNITIES AND CHALLENGES IN CLINICAL IMPLEMENTATION OF A MULTI-OMICS SEQUENCING APPROACH. (23rd April 2019) - Jain, Payal; Mueller, Sabine; Liang, Winnie S; Panditharatna, Eshini; Zhang, Bo; Zhu, Yuankun; Kambhampati, Madhuri; Kline, Cassie; Kilburn, Lindsay; Gupta, Nalin; Yang, Xiaodong; Nazemi, Kellie; et al.
Abstract: BACKGROUND: Diffuse intrinsic pontine glioma (DIPG) is an infiltrative, inoperable midline tumor with devastating outcomes. We have recently completed a prospective clinical trial for children and young adults with newly diagnosed DIPG that included clinical whole exome sequencing (WES) and RNA sequencing (RNAseq) of tumors and development of a personalized treatment plan. In this study, we retrospectively expanded sequencing efforts to include whole genome sequencing (WGS) and methylation profiling of paired tumor/normal (T/N) samples as well as longitudinal tumor specimens. We sought to perform a pan-omics analysis to determine which sequencing platform combination could most benefit patient outcomes in future precision medicine DIPG trials. METHODS: Thirty-three DIPG patients underwent successful biopsy in PNOC003. Clinical WES/exome panel sequencing and RNAseq was generated for 30 primary tumors and 2 progression tumors. We performed research-based WGS and methylation profiling of all tumors to do a pan-omics analysis. Cross-platform analysis was performed to compare WGS and WES and define additional mutations. RESULTS: In addition to WES and RNAseq, we performed WGS on all 33 primary T/N pairs, 2 progression samples, and 3 autopsy samples. Methylation profiling was done on 30 primary, 1 recurrent and 6 autopsy tumor samples. WGS identified all the actionable coding alterations called by WES and further identified non-coding variants of potential clinical significance. A pan-omics analysis spanning WGS, WES, RNAseq and methylation data is being performed. Tumor evolution was demonstrated by longitudinal comparison of genetic alterations across primary, recurrent and autopsy tumor samples to highlight tumor-intrinsic versus treatment-driven alterations in DIPGs. DISCUSSION: The ongoing pan-omic analysis from PNOC003 has begun informing the next generation of molecularly-driven DIPG clinical trials by suggesting inclusion of WGS in clinical sequencing panels as well as offering additional insights into the diverse mutational landscape of DIPGs.